Effect of cryopreservation on in vitro maturation and cleavage rate of immature prepubertal goat oocytes - SINHA, RAJNI; KHARCHE, S D; SINHA, N K; GOEL, A K; JINDAL, S K; SARASWAT, SONIA (The Indian Journal of Animal Sciences, 2013)
The present study was conducted to evaluate effects of cryopreservation on the morphology, maturation rate and developmental capacity of immature prepubertal goat oocytes subjected to vitrification and slow freezing method. The proportion of immature oocytes recovered in a morphologically normal state was significantly higher for control than those for vitrification and slow freezing method. Following in-vitro maturation, the nuclear maturation rate was significantly higher for control (29.70%) than those for vitrified (9.80%) and slow freezing (18.18%) method. The percentage of normal in vitro matured oocytes following thawing in vitrification and slow freezing groups were 53.73% and 80.00%, respectively. A significant difference was observed in the cleavage rate 48 h post insemination, among vitrification, slow freezing and control were 2.0, 5.80 and 13.58%, respectively. The results indicated that the cleavage rates of oocytes in vitrification and slow freezing method did not differ significantly but differ signitificantly (P<0.05)with control groups.